Transparency, price-dependent demand and product variety - Yiquan Gu; Tobias Wenzel (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2010)
This paper revisits the relationship between transparency on the consumer side and product variety as analyzed in Schultz (2009). We identify two welfare effects of transparency. More transparency decreases price-cost margins which is beneficial forwelfare. On the other hand, more transparency reduces variety which can be positive or negative for welfare. Overall, more transparency is always welfareimproving.
Keywords: L13; L15; L40; 330; Market Transparency; Product Variety; Salop Model; Produktdifferenzierung; Marktstruktur; Information; Marktmacht; Wohlfahrtseffekt; Theorie